Diversities of chromite mineralization induced by chemo–thermal evolution of the mantle during subduction initiation - Peng-Fei Zhang; Mei-Fu Zhou; Paul T. Robinson; John Malpas; Graciano P. Yumul; Christina Yan Wang; Jie Li (Nature Communications)
Abstract Ophiolites, mostly formed via subduction initiation at proto-forearcs, exhibit a unique variation of mantle-derived magmatism from MORB-like to low-Ti tholeiitic and boninitic-like affinities. Such variation was suggested to form chromite deposits spanning high-Al to high-Cr types. Nevertheless, the origin of diverse magmatism during subduction initiation and their linkages to different chromite deposits has long been enigmatic. Here we show elemental and Os isotopic compositions of different chromitites from the Zambales ophiolite, Philippines. Combined with data from ophiolites worldwide, high-Al and high-Cr chromitites are revealed to result from low-Ti tholeiitic and boninitic-like magmatism, respectively. Proto-forearc mantle had few chromitites generated during MORB-like magmatism, but afterwards, it was modified first by slab fluids and later by continuous asthenospheric upwelling in the context of slab densification and rollback. The latter modification elevated the geothermal gradient and replenished fertile components in the proto-forearc mantle progressively, inducing increasingly higher degrees of mantle melting and Cr-richer magmatism and chromitites.